Assessing the impact of Islamic microfinance on poverty alleviation in Northern Nigeria - Gumel, Gambo; Md Saad, Norma; Kassim, Salina (Islami Bank Training and Research Academy, 2014)
Nigeria is one of the leading economies in Africa endowed with vast oil reserve and abundant human and material resources. Despite these resources, poverty among the populace is widely spread. The National Planning Commission in Nigeria in 2012 reported that more than 75 million people are trapped by poverty. Several efforts have been put forward at various points in time by successive governments, private entrepreneurs and other development partners to overcome the menace of poverty among the populace. Recently, the Islamic microfinance becomes a mechanism through which poverty is being challenged aswitnessed in some Muslim countries such as Bangladesh, Malaysia, and Pakistan. The purpose of this study is to examine the role of Islamic mircofinance products on poverty alleviation in northen part of Nigeria. The study used recipients of Islamic loan from some selected microfinance banks in Kano and Jigawa states of Nigeria. A total of 400 samples drawn from beneficiaries of Islamic microfinance loan through simple random sampling were used. Questionnaires were used and the data generated were analyzed using Pearson correlation analysis. The findings of the study has also identified that amount of Islamic loan, age, level of education, and gender as important variables for increasing household income. Microfinance regulators or policy makers (Central Bank of Nigeria) will also make use the findings of this study in designing policy framework for microfinance institutions in Nigeria.